Sleeping with the Tyrant: Thebe the Tyrannicide and the Death of Alexander of Pherae in Plutarch’s Pelopidas - Boyd, Marcaline J. (Histos, 2021)
The murder of Alexander of Pherae by his wife Thebe closes Plutarch’s Pelopidas. While scholars have tended to view this ending as posthumous vengeance for Plutarch’s hero, this paper argues that Plutarch wrote Alexander’s death to satisfy the quintessential elements which a wicked tyrant ought to experience and that he also exercised creativity by adducing another motif of Thebe as noble tyrannicide. Plutarch’s take, therefore, departed from an established tradition which portrayed Thebe unfavourably. A virtuous Thebe complemented Plutarch’s interest in other female tyrannicides in Mulierum Virtutes as well as his position expressed in that treatise that bravery is not gender-specific.